Boosted Tipranavir versus Darunavir in Treatment-Experienced Patients: Observational Data from the Randomized POTENT Trial - Elgadi, Mabrouk M.; Piliero, Peter J. (Drugs in R&D, 2011)
Background: The POTENT trial compared the safety and efficacy of tipranavir/ritonavir (TPV/r) to darunavir/ritonavir (DRV/r), each with an optimized background regimen (OBR) in triple-class experienced HIV-1-infected patients with resistance to more than one protease inhibitor (PI). Methodology/Principal Findings: POTENT was a prospective, open-label study of triple-class (PI, non-nucleoside reverse transcriptase inhibitors [NNRTI], nucleoside reverse transcriptase inhibitors [NRTI]), treatment-experienced, HIVpositive patients. Subjects were randomized to either TPV/r (500/200mg twice daily) or DRV/r (600/100mg twice daily) on a genotype-guided, investigatorselected OBR. CD4+ counts andHIV viral loads were assayed at key timepoints. The primary endpoint was time to virologic failure (viral load >-500 copies/mL). POTENT was prematurely terminated due to slow enrollment. Thirty-nine patients were treated with either TPV/r (n= 19) or DRV/r (n= 20); 82% were male, 77%White, with mean age of 43.6 years. Mean baselineHIV RNA was 3.9 log10 copies/mL.Median prior antiretrovirals was 11, with no prior raltegravir or maraviroc exposure. Raltegravir was the most common novel class agent in the OBRs (n = 14 TPV/r; n = 12DRV/r). In both groups, patients achieved mean viral load decreases >-2 log10 copies/mL by week 8, and by week 12 mean CD4+ counts rose by 40–50 cells/mm 3 . Total observation time was 32 weeks. Drug-related adverse events were reported in 21% (TPV/r) and 25% (DRV/r) of patients. Conclusions/Significance: TPV/r- and DRV/r-based regimens showed similar short-term safety and efficacy. These data support the use of next-generation PIs such as tipranavir or darunavir with novel class antiretroviral agents (integrase inhibitors, CCR5 antagonists, or fusion inhibitors). Trial Registration: Clinicaltrials.gov NCT00517192